Financial literacy on behavioral biases and risk avoidance towards investment decisions - Wijayanti, Ratna; Hatta, Madani; Sriwidharmanely, Sriwidharmanely; Bhayangkari, Audina Dwi (Proceeding International Conference on Accounting and Finance, 2024)
This research aims to determine the influence of behavioral biases, and risk avoidance on investment decisions through financial literacy women entrepreneurs in Bengkulu Province. These researches used primary data obtained through questionnaire. The population in this study is women entrepreneurs in Bengkulu Province, and the sampling technique used is snowball sampling. The data obtained was analyzed using SmartPLS 4.0 software. The results suggest that investment decisions are affected by financial literacy and overconfident bias, but representativeness bias, anchoring bias, availability bias, and risk avoidance don’t directly affect investment decisions. And availability bias, overconfidence bias, representativeness bias, and risk avoidance can affect financial literacy, but anchoring bias cannot affect financial literacy. As well as financial literacy can mediate the interaction of overconfident bias, representativeness bias, availability bias, and risk avoidance, investment decisions. In addition, financial literacy hasn’t been able to mediate the interaction among anchoring bias and indirect investment decisions.